Determine the most appropriate time period for the concentration of lactic acid in the blood after a competitive effort for handball players aged 14-15 years. - مصطفى , عكاب (Journal of Sport Science Technology and Physical Activities, 2025)
The research aims to “identify the most appropriate time period, based on multiple times (1, 3, 5) minutes, to monitor the concentration of lactic acid in the blood after exercise. To achieve the goal, the researcher used the descriptive (semi-experimental) method in a comparative manner to suit it with the problem and objectives of the research. The research sample was chosen intentionally, and they are the research population of players from the National Center for Sports Talent Welfare in handball, aged (15-17) years in Baghdad, The research sample consisted of (10) representative players, and the sample was chosen intentionally for a year. The researcher conducted the test and measured the lactic acid concentration after (1, 3, 5) minutes after effort. The appropriate statistical treatments were conducted. The researcher concluded from his research that the most appropriate time for the highest level of lactic acid concentration in the blood of handball players after effort is (5) minutes. The level of lactic acid concentration increases with the increase in intensity that accompanies the organized training process during a specific training period. Accordingly, the researcher recommends that coaches and researchers should adopt minute (5) when measuring lactic acid to regulate training loads and know the intensity of training in order to develop handball players